Collaborative script writing for a digital media project. (23rd February 2016) - Miller, Lindsay
Abstract : Writing in a second language, especially using new technologies, is fraught with difficulties for most students. There are two main challenges, firstly, how can students move from their understanding of the mechanical aspects of texts (good sentence structure and appropriate lexis) to deal with issues of how to construct texts that go beyond the basics, for instance drawing upon multiple modes of expression, and secondly, how can students use their knowledge about new technologies to help them create texts? This paper examines the collaborative processes English for Science students go through when constructing a scientific text for a popular audience, here, a digital video scientific documentary. Undergraduate students had to work in groups to write the text for a digital story based on an experiment they had undertaken. As part of the process these students had to prepare a script which was then recorded, either speaking directly to the camera, or as a voice over onto the video to complement their video images. Based on examples from the students' generated data: Facebook, WhatsApp posts and scripts, we see that the end product was rich and informative. It is maintained that a collaborative approach using new technologies to writing such popular scientific texts engages the students with their work and that, when given the opportunity, they learn from each other as much as from their teacher.